Remote sensing of cometary bow shocks: modelled asymmetric outgassing and pickup ion observations. Issue 4 (10th July 2021) - Alho, Markku; Jarvinen, Riku; Simon Wedlund, Cyril; Nilsson, Hans; Kallio, Esa; Pulkkinen, Tuija I
ABSTRACT: Despite the long escort by the ESA Rosetta mission, direct observations of a fully developed bow shock around 67P/Churyumov–Gerasimenko have not been reported. Expanding on our previous work on indirect observations of a shock, we model the large-scale features in cometary pickup ions, and compare the results with the ESA Rosetta Plasma Consortium Ion Composition Analyser ion spectrometer measurements over the pre-perihelion portion of the escort phase. Using our hybrid plasma simulation, an empirical, asymmetric outgassing model for 67P, and varied interplanetary magnetic field (IMF) clock angles, we model the evolution of the large-scale plasma environment. We find that the subsolar bow shock standoff distance is enhanced by asymmetric outgassing with a factor of 2 to 3, reaching up to 18 000 km approaching perihelion. We find that distinct spectral features in simulated pickup ion distributions are present for simulations with shock-like structures, with the details of the spectral features depending on shock standoff distance, heliocentric distance, and IMF configuration. Asymmetric outgassing along with IMF clock angle is found to have a strong effect on the location of the spectral features, while the IMF clock angle causes no significant effect on the bow shock standoff distance. These dependences further complicate the interpretation of the ion observations made by Rosetta . Our data-model comparison shows that the large-scale cometary plasma environment can be probed by remote sensing the pickup ions, at least when the comet's activity is comparable to that of 67P, and the solar wind parameters are known.